Conceptul de istorie literară - Ioana Mircea (Revista de Istorie și Teorie Literară)
This paper offers an overview on the concept of literary history: the presentation opens with the returning to two classic definitions of it and with the identification of its dual character, objective and subjective. In order to study the subject, revived after the 1990s, one must first clearly define literary theory, critique, and history; decide whether they are complementary or contradictory; and see how literary science interacts with the concept. We can identify a hierarchy in which theory comes first, critique second and history last, and then examine the adaptation of dichotomies and the way in which literary history is perceived by various Romanian authors.